Bioresorbable scaffolds: a new paradigm in percutaneous coronary intervention. Issue 1 (December 2016) - Tenekecioglu, Erhan; Farooq, Vasim; Bourantas, Christos; Silva, Rafael; Onuma, Yoshinobu; Yılmaz, Mustafa; Serruys, Patrick
Abstract Numerous advances and innovative therapies have been introduced in interventional cardiology over the recent years, since the first introduction of balloon angioplasty, but bioresorbable scaffold is certainly one of the most exciting and attracting one. Despite the fact that the metallic drug-eluting stents have significantly diminished the re-stenosis ratio, they have considerable limitations including the hypersensitivity reaction to the polymer that can cause local inflammation, the risk of neo-atherosclerotic lesion formation which can lead to late stent failure as well as the fact that they may preclude surgical revascularization and distort vessel physiology. Bioresorbable scaffolds overcome these limitations as they have the ability to dissolve after providing temporary scaffolding which safeguards vessel patency. In this article we review the recent developments in the field and provide an overview of the devices and the evidence that support their efficacy in the treatment of CAD. Currently 3 devices are CE marked and in clinical use. Additional 24 companies are developing these kind of coronary devices. Most frequently used material is PLLA followed by magnesium.